Bemerkungen zur geomorphologischen Kartierung 1 : 25 000 in der Bundesrepublik Deutschland am Beispiel des Blattes 7520 Mössingen (Kreis Tübingen; Baden-Württemberg) - Leser, Hartmut (ERDKUNDE, 1975)
The Mössingen sheet is used as the example in a discussion of the Key to the Geomorphological Detail Map 1:25,000 of the Federal Republic of Germany. In contrast to the map sheet presented here, this Key will show morphographic and morphogenetic content. This concept is deliberately compared to an exclusively morphographic map. The wealth of information on the Mössingen map shows that a comprehensive recording of the morphographic situation at 1:25,000 scale is both possible and can be done in a cartographically satisfying and technically straightforward way. If, in addition, the most important morphogenetic phenomena are shown in detail, difficulties of content and cartography are raised. These could only be resolved by reducing the total content of the map. This would however reduce the map’s value, assuming that the morphographic information is as important for theory con struction within geomorphology as it is for practical application outside the discipline.